Evaluation of the Efficacy of Liposomal Bupivacaine in Total Joint Arthroplasty. (June 2021) - Zamora, Francis J.; Madduri, Rani P.; Philips, Ashmi A.; Miller, Nancy; Varghese, Mini
Background: Appropriate pain control is one of the cornerstones necessary to promote positive clinical outcomes. A new bupivacaine liposomal formulation was designed to extend its analgesic effect for up to 72-hours post-surgery, reportedly leading to significant opioid-sparing. Method: Retrospective and prospective chart review conducted in a 178-bed academic institution between January 2013 to December 2013 and August 2014 to November 2014, in 115 patients that receive hip and knee arthroplasty. The primary outcome was the measurement of average daily pain score on post-operative days 1 and 2. Secondary outcomes included length of stay, overall opioid use post-surgery and pain control satisfaction using Press-Ganey® scores. Results: The average pain scores in the HCl group were 4.64 and 4.38 (Likert score: 0-10) for POD 1 and POD 2, compared to 4.72 POD 1 and 4.2 POD 2 in the liposome group (POD 1: p = 0.413; POD 2: p = 0.303). The difference in LOS for knee arthroplasty was statistically significant [HCl group: 1.94 days (± 0.66) versus liposome group: 2.27 days (±0.77) p -value = 0.038)] favoring the standard of care. For hip arthroplasty or bilateral knee arthroplasty the differences in LOS were not statistically significant ( p = 0.052 and p = 0.484 respectively). 93% of the patients in the HCl group, pain was well controlled, versus 88.5% in the liposome group with similar oxycodone IR use among groups. Conclusion: Liposome bupivacaine did not offer a notable benefit compared to the HCl formulation in our study.